Um patrimônio “adormecido”: a cultura material arqueológica pré-colonial nos lugares de memória do Vale do Taquari/RS - Schneider, Patrícia (2010)
This study handles over the appreciation of the precolonial archaeological heritage, placed in institutions of preservation, guard and exposition of three towns in Vale do Taquari/RS region. The three selected towns are Arvorezinha, Lajeado e Taquari and the institutions are, respectively, the Museu Municipal de Arvorezinha; Museu Histórico Bruno Born; Casa Costa e Silva. The main purpose of the present research is to diagnose the space and the treatment dispensed to precolonial material culture in these places of remembrance and to verify if they receive a different treatment in relation to historical materials. The study was accomplished through data collection, based on field research method, with the filling out of a diagnosis form, previously elaborated. The result achieved suggests that, in the institutions researched, the archaeological materials are discredited, in opposition to the historical ones, and they aren't correctly contextualized, being observed as curious and eccentric objects, without any relation to the local community.